Construindo pontes para uma educa??o antirracista: forma??o continuada de professores de matem?tica na perspectiva das rela??es ?tnico-raciais - Calado, Tha?s Santana Ara?jo (2024)
Given the structural and structuring context of racism in Brazilian society, the population increasingly needs anti-racist training, guided by public policies already in force, as well as others that still need to be considered. To achieve this, teacher training is necessary in all areas, also guided by this perspective. So, here we seek to understand how discussions regarding ethnic-racial relations take place in the continuing education policy based on courses and programs that mathematics teachers from Feira de Santana participated in. From this, as a research problem, we have: how do discussions regarding ethnic-racial relations take place in the continuing education policy based on courses and programs that mathematics teachers from Feira de Santana participated in? Thus, it is characterized as a bibliographical research, of a documentary, exploratory and descriptive nature, developed from a qualitative approach and will use the lenses of Anti-Racist Education, Critical Mathematics Education and Critical Theory, using content analysis as a method. With this, documents, public policies and laws that support the courses and continuing education programs mentioned through the online questionnaire were analyzed. In this way, it was possible to understand that, despite the great advances compared to the initial training of mathematics teachers, there are still gaps in continued training with regard to the guidelines of education for ethnic-racial relations and Critical Mathematics Education, which is even more distant from the training process of these professionals.